Analysis of the Maudhu'i Tafsir: Mahabbah's Orientation in the Light of Al-Qur'an - Sukiyat Sukiyat; Miftah Ulya; Nurliana Nurliana; Edi Hermanto; Abd Ghofur (Jurnal Ushuluddin, 2022)
The Qur'anic explains that in humans there is a feeling of mahabbah which is interpreted as love. The urgency of love is very fundamental in the human journey, both love between fellow human beings, nature and the environment, even more important is love for Allah swt. Mahabbah which is understood with love is loving deeply as a feeling of longing and happy for something. This feeling then causes a person to focus on him and even encourage him to give the best, in the form of love and affection.  This research method is through interpretation using the maudhu'i interpretation method, which is qualitative in nature to be analyzed inductively, and the results of the research emphasize the meaning of generalization. Through an approach in the form of library research, it is formulated in an analytical descriptive style to obtain a conclusion. The final result of this study confirms that the orientation of human mahabbah is oriented to three categories. First, man's allegiance to something pleasant. Second, human love for something valuable, Third, human love for the existence of a common perception. From all that is done, it will produce an attitude and a sense of mahabbah that is framed with Islamic values that are constantly oriented to self-servitude to Allah swt. while being oriented towards tolerance, humanization, in a pluralistic society